Living and Working with the New Medical Technologies: Intersections of Inquiry - Barber, C. R. (Journal of medical ethics, 2002)
This collection of essays is the outcome of a conference addressing the problems arising from the conjunction of medicine and the humanities with the ever more pressing concerns of bioethics. Since this is a fairly recent development the introduction summarises the argument about what constitutes science and whether it is culturally located. Throughout this well-produced book there is room for discussion and dispute as is inevitable in any interdisciplinary work.The first part of the book lays the theoretical foundations. Rheinberger discusses the enormous change in the ability to control the biological make up of mankind that molecular medicine and gene therapy offer. This will effectively end the nature/culture juxtaposition. These deliberations are then placed into a philosophical perspective by Rabinow.Part 2 moves …